CONTRIBUTIONS OF SUPERVISED INTERNSHIP TO THE CONSTRUCTION OF PROFESSIONAL IDENTITY OF FUTURE TEACHERS - Ferronatto, Eliane Terezinha Tulio (Seven Editora, 2025)
The research entitled "Contributions of the Supervised Internship for the construction of the professional identity of future teachers" aims to identify and understand how the construction of the professional identity of teachers is perceived, through analysis of the final reports of the Supervised Internship of the Initial Years of Elementary Education and the method called the tree of life (ADV), which configures the roots of the tree with the base: the academics related the people, events, ideas that contributed to the decision to choose the course; the trunk refers to the actions: skills, interests and events that supported them to continue in the course; and the leaves and fruits that represented the dreams: expectations and perspectives after graduation. Twelve (12) 4th-year interns of a Pedagogy Course (last year of the Course) at a public University in the interior of Mato Grosso do Sul participated in this research. We found that the Supervised Internship, when carried out with seriousness and commitment, is an excellent tool for the construction of identity constitution processes, as it relates to the singularity of the socialization processes experienced by each intern, causing oscillations, contradictions, permanences and changes in the conceptions and values attributed to being a teacher.DOI: https://doi.org/10.56238/sevened2025.030-005